A teoria das virtudes de Alasdair MacIntyre - Flora Rocha Cardoso (2010)
This dissertation aims to study Alasdair MacIntyre's virtue theory as presented in After Virtue (1981). In order to achieve this, an introduction to his criticism of the Enlightenment project's justification of morality, in addition to his criticism of emotivist ethical theory, will be required. His adoption of Aristotle's virtue theory will also be covered, as well as (some of) the criticism directed at the consequences of the MacIntyrian theory and the answer given by the author in his Poscript (1984)